Anesthesia of Epinephelus marginatus with essential oil of Aloysia polystachya: an approach on blood parameters - Fogliarini, Carine O. (2018)
This study investigated the anesthetic potential of the essential oil (EO) of Aloysia polystachya in juveniles of dusky grouper (Epinephelus marginatus). Fish were exposed to different concentrations of EO of A. polystachya to evaluate time of induction and recovery from anesthesia. In the second experiment, fish were divided into four groups: control, ethanol and 50 or 300 mu L L-1 EO of A. polystachya, and each group was submitted to induction for 3.5 min and recovery for 5 or 10 min. The blood gases and glucose levels showed alterations as a function of the recovery times, but Na+ and K+ levels did not show any alteration. In conclusion, the EO from leaves of A. polystachya is an effective anesthetic for dusky grouper, because anesthesia was reached within the recommended time at EO concentrations of 300 and 400 mu L L-1. However, most evaluated blood parameters showed compensatory responses due to EO exposure.